Gas-to-Particle Conversion in Surface Discharge Nonthermal Plasmas and Its Implications for Atmospheric Chemistry - Hyun-Ha Kim; Atsushi Ogata (Sensors, 2011)
This paper presents some experimental data on gas-to-particle conversion of benzene using nonthermal plasma (NTP) technology and discusses the possibility of its technical application in atmospheric chemistry. Aerosol measurement using a differential mobility analyzer (DMA) revealed that the parts of benzene molecules were converted into a nanometer-sized aerosol. Aerosol formation was found to be highly related with the missing part in carbon balance. Scanning electron microscopy analysis showed that the aerosols formed in synthetic humid air are the collection of nanoparticles. The carbonyl band (C=O) was found to be an important chemical constituent in the aerosol. The potential of the NTP as an accelerated test tool in studying secondary organic aerosol (SOA) formation from VOCs will be also addressed.